Traditional Sports, Indigenous Heritage, and Tourism Branding: Pè-sapèan Bangkalan in Madura, Indonesia - Anwar, Khoirul; Pujiati, Amin; Prajanti, Sucihatiningsih Dian Wisika (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Tourism branding in the sports industry shows positive labeling that is used to attract public interest from tourist destinations. It becomes interesting when pè-sapèan can combine sports, cultural heritage and attractions in tourism branding. The method used is to use a systematic literature review to analyze potential opportunities for traditional sports, traditional heritage and tourism branding by collecting articles via Google Scholar. Events in the world of sports industry need a platform as a means to develop into an industrial orientation. In Bangkalan Regency, the annual event that is always held is the Traditional Sports Festival. This Traditional Sports Festival event is not only a place to exercise together but also to encourage enthusiasm, contribution and collaboration to jointly preserve traditional games, especially in Bangkalan, namely Pè-sapèan Bangkalan. In Bangkalan, various sporting events, such as the DISPORA CUP and the DISBUDPAR CUP are still ongoing, this is clear evidence that the development of sports marketing still exists and continues to increase. The traditional Pè-Sapèan sports game was often played by children in the past on Salt Island, with a minimum of three people playing. The game is a replica of Madurese culture, Kerapan Sapi. However, the cow and the jockey both use people, so the game pattern; starting from the start line to the finish line. The team that arrives first is the winner. The traditional sports game Pè-Sapèan can be interpreted as having become extraordinary capital to be developed to preserve the traditional heritage of Bangkalan Regency. This will be a forum for continuing livelihoods by combining cultural heritage capital and community self-organization. Pè-Sapèan traditional sports games can increase the community's self-control capacity towards traditional heritage assets. It would be a win-win if the role of local government could be to develop sports tourism resources, improve sports tourism services, and appoint functional government departments in building tourism branding.